Report My Signals - Brett-James, Antony (London George G. Harrap & Co. Ltd, 1948)
Account of service with the 5th Indian Division Signals in the Western desert at Alamein and in Burma.
Includes Illustrations, Index and Maps
Keywords: India. -- Army. -- 5th Division -- World War, 1939-1945 -- Regimental histories -- India -- World War, 1939-1945 -- Communications